Creativity in SMEs: A overview and agenda for future research - Mauricio Castillo-Vergara; Domingo García Pérez de Lema (BBR: Brazilian Business Review)
In the last decades, the interest in creativity has grown significantly; its importance is related to the impact on the performance of companies since creativity is defined as the root of innovation. Even though research has been quite fruitful in many disciplines, its study in small and medium enterprises has been less explored. This article reviews the literature on creativity in small and medium enterprises and aims to establish proposals for future research. A bibliometric analysis was developed to achieve the objective mentioned above, considering the construction of scientific maps, performance analysis, and graphic maps. Additionally, a content analysis of the selected articles to establish the variables studied around creativity. The study has shown that it is necessary to increase research on creativity in small and medium businesses in a wide variety of topics. Therefore we offer a valuable framework to resolve existing gaps and guide future researchers.